Terrorism: a history - Law, Randall D. (Themes in history series, 2024)
"In this third edition of his widely acclaimed survey, Randall D. Law makes sense of the history of terrorism by examining it within its broad political, religious and social contexts from the ancient world to the present day. It remains the go-to book for those wishing to understand the real nature and importance of this ubiquitous phenomenon"--